ЁНҒИН ХАВФСИЗЛИГИ ҚОИДАЛАРИНИНГ БУЗИЛИШИ: ҲУҚУҚБУЗАРЛИК ВА ДАВЛАТ ЁНҒИН НАЗОРАТИ ФАОЛИЯТИНИ ТАКОМИЛЛАШТИРИШ МАСАЛАЛАРИ - Қурбонов, Х.А. (SCIENCE and SOCIETY, 2020)
The article deals with the study of a number of articles dealing with State Fire Inspection Authorities in the Code of the Republic of Uzbekistan on Administrative Liability are considered in depth, and examples from the experience are also analyzed. The author puts forward a number of comprehensively thought-out proposals for improving the activities of employees of the State Fire Safety Service in the Republic of Uzbekistan.